A comparative study of urban and rural dairy management systems in Sudan - Kulneff, Cecilia (2006)
Sudan is one of the poorest countries in the world, situated in the north-eastern Africa, with a nature ranging from desert in the north to tropical rainforest in the south. The majority of the population, of over 36 million people, is settled in central urban areas, resulting in great demands of food supply, including dairy products. The objectives of the present paper was to, by help of interviews and observations, study Sudanese cattle dairy production systems near Khartoum and in the Agalyeen area, Gezira state, with respects to breeds, general management, water regime and feeding of cows and calves.